The dynamics of target fishes resources in coral reef fisheries at coastal area of Ternate Island - Faizal Rumagia; Mennofatria Boer; Rahmat Kurnia; Mohammad Mukhlis Kamal (Depik, 2019)
Abstract. As one of the coastal ecosystem, coral reef ecosystem is a magnificent marine ecosystem, where their species richness and composition play an important role for the ability of coral reef ecosystem to respond to the fishing activity and other stressors, where fishing has impacted the fish community, target or non-target reef fish species. The dynamic of reef fish resources, especially the target species, become one of the aspects that must be considered in the management and utilization of the fisheries resources in the coral reef ecosystem and their surrounding area. The purpose of the study was to analyze the dynamics of the target fish in the coral reef fishing activity at the coastal area of Ternate Island, from the growth, mortality and exploitation ratio aspect. The research was conduct from April to August 2018 in the coastal area of Ternate Island. The data sampling was growth parameters data through length and weight measurement. Total sample measure along the research time was 6245 sample (consist of seven family and 11 species). The result shows that the target fish have asymptotic length (L∞) range from 263.16–483.16 mm, with growth coefficient (K) ranging from 0.61–0.92 per year. The theoretic age at length 0 (t0) ranges from minus 0.0825–0.1669 year (equal to 30-61 day). The fishing mortality rate (F) is lower than the natural mortality rate (M), which resulting the exploitation rate (E) for the target fish mostly under 50%, which indicated that the utilization of the reef fishes in the coastal area of Ternate Island is still under-exploited.Keywords: Exploitation rate, Growth parameters, Length-weight relationship, Mortality rate, Stock assessment